Intra-Urban Spatial Inequality : Cities as "Urban Regions" - Kilroy, Austin (Washington, DC: World Bank, 2012)
This paper explores spatial inequalities within cities: how they are generated, what characteristics they have, and how these spatial inequalities become persistent and self-perpetuating, embodying serious economic and social problems. This conceptual frame views cities as agglomerations of 'urban regions'--which exhibit significant spatial intra-urban inequalities, and where trends towards equality are constrained predominantly by labor immobility and land-use policies. One of the meta-insights of this paper is that urban problems are often made worse when they coexist and overlap in space. It shows how spatial inequalities are a structural cause of their own perpetuation, and to suggest policies that go beyond neighborhood interventions.